3-D Time-Accurate CFD Simulations of a Multi-Megawatt Slender Bladed HAWT under Yawed Inflow Conditions. (September 2016) - Sayed, M.; Lutz, Th.; Krämer, E.
Abstract: In the present study numerical investigations of a generic Multi-Megawatt slender bladed Horizontal-Axis Wind Turbine (HAWT) under yawed inflow conditions were conducted. A three-dimensional URANS flow solver based on structured overlapping meshes was used. The simulations were conducted at wind speeds of 7m/sec, 11 m/sec and 15 m/sec for different yaw angles ranging from +60° to -60°. It was concluded that, for below rated wind speeds, under small yaw angles (below ±15°) the magnitudes of the blade forces are slightly increased, while under high yaw angles (above ±15°) there is a significant decrease. Moreover, the load fluctuations, for the different yaw angles, have the same frequency but different amplitude and oscillation shape. It was concluded that at the above rated wind speed of 15 m/sec, the blade aerodynamic loads are significantly affected by the yaw inflow conditions and the magnitude values of the loads are decreased with increasing yaw angle. It can be concluded that the angle of attack and the tower interference are the utmost variables affecting the yawed turbines.